2022
DOI: 10.3390/antiox11101863
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Unloaded and Curcumin-Loaded Solid Lipid Nanoparticles on Tissue Transglutaminase Isoforms Expression Levels in an Experimental Model of Alzheimer’s Disease

Abstract: Alzheimer’s disease (AD) is a neurodegenerative disease representing the most prevalent cause of dementia. It is also related to the aberrant amyloid-beta (Aβ) protein deposition in the brain. Since oxidative stress is involved in AD, there is a possible role of antioxidants present in the effected person’s diet. Thus, we assessed the effect of the systemic administration of solid lipid nanoparticles (SLNs) to facilitate curcumin (CUR) delivery on TG2 isoform expression levels in Wild Type (WT) and in TgCRND8 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 50 publications
0
9
0
Order By: Relevance
“…The systemic administration of SLNs-CUR, both in WT and in Tg mice, allows one to differently modulate TG2 isoforms, which act either on apoptotic pathway activation or on the ability of the protein to repair cellular damage in the brains of Tg mice. In this study, it was also suggested that SLNs-CUR could be an innovative tool for the treatment of AD (180).…”
Section: Curcumin and Alzheimermentioning
confidence: 79%
See 2 more Smart Citations
“…The systemic administration of SLNs-CUR, both in WT and in Tg mice, allows one to differently modulate TG2 isoforms, which act either on apoptotic pathway activation or on the ability of the protein to repair cellular damage in the brains of Tg mice. In this study, it was also suggested that SLNs-CUR could be an innovative tool for the treatment of AD (180).…”
Section: Curcumin and Alzheimermentioning
confidence: 79%
“…Furthermore, Campisi et al (180) assessed the effect of the systemic administration of SLNs to facilitate Cur delivery 10.3389/fnut.2022.1040259 on TG2 isoform expression levels in Wild Type (WT) and in TgCRND8 (Tg) mice. An experimental model of AD, which expresses two mutated human amyloid precursor protein (APP) genes, was used.…”
Section: Curcumin and Alzheimermentioning
confidence: 99%
See 1 more Smart Citation
“…Campisi et al [ 58 ] studied the effects of systemic administration of C-SLN on the delivery of CUR to neuronal cells and the levels of expression of the tissue transglutaminase isoform (TG2) in an experimental model of AD. After the interventions, the animals underwent a behavioral descent test to assess memory and learning.…”
Section: Cur a Phenolic Compound Derived From Curcuma Longamentioning
confidence: 99%
“…To eliminate these drawbacks, solid nanoparticles and nanostructured lipid carriers were created in the 1990s. Phytochemicals such as quercetin [ 251 ], curcumin [ 252 ], or resveratrol delivered via solid nanoparticles showed increased and sustained levels of the drug in the brain with reduced formation of Aβ [ 252 , 253 ]. Nanostructured lipid carriers have also been successfully employed to deliver resveratrol [ 254 ] or curcumin for diminishing Aβ toxicity and improving the symptoms in AD models [ 255 ].…”
Section: Novel Therapeutic Strategies In Alzheimer’s Diseasementioning
confidence: 99%